2012
DOI: 10.1002/star.201200100
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fermentation of a retrograded maize starch by healthy adult fecal extract and impacts of exogenous microorganisms on three acids production

Abstract: The impacts of 14 exogenous microorganisms on simulated colonic fermentation and acid production of a retrograded maize starch were studied in the present work. A commericial high‐amylose maize starch (Hylon VII) was treated by three autoclaving–cooling cycles. The obtained retrograded starch contained RS of 29.4% w/w, was used as RS‐containing substrate for an in vitro fermentation by healthy adult fecal extract at 40 g/L and 37°C for 36 h. GC analysis showed that acetic, propionic and butyric acid generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Zhou et al (2013) reported that the production of SCFAs (especially of butyric acid) was greatly enhanced by fermentation time. When retrograded maize starch and maize RS were fermented by human intestinal microflora, certain exogenous microorganisms had beneficial effects on acid production, especially butyric acid Zhu and Zhao 2013). The results obtained in this study were consistent with those reported by other researchers; i.e., probiotics enhanced the production of acetic and butyric acid during the colonic fermentation of RS.…”
Section: Impacts Of Probiotics On Acid Productionsupporting
confidence: 91%
See 1 more Smart Citation
“…Zhou et al (2013) reported that the production of SCFAs (especially of butyric acid) was greatly enhanced by fermentation time. When retrograded maize starch and maize RS were fermented by human intestinal microflora, certain exogenous microorganisms had beneficial effects on acid production, especially butyric acid Zhu and Zhao 2013). The results obtained in this study were consistent with those reported by other researchers; i.e., probiotics enhanced the production of acetic and butyric acid during the colonic fermentation of RS.…”
Section: Impacts Of Probiotics On Acid Productionsupporting
confidence: 91%
“…fermentation of maize RS and retrograded maize starch by fecal human extracts Zhu and Zhao 2013). These results suggest that certain RS-microorganism combinations could contribute to high acid production levels in the large intestine.…”
mentioning
confidence: 82%
“…The later two researches prove that microorganisms have different ability to degrade RS into SCFAs, and provide support to the present study. It is also found in another research that E. faecalis, E. faecium, B. infantis, and B. longum can cooperate well with adult fecal extract to favor propionic and butyric acid formation from a retrograded starch containing RS [20]. This finding also gives support to the present result.…”
Section: Impacts Of Exogenous Microorganism or Strain Combination On supporting
confidence: 90%
“…The two acids was analyzed with the same procedure and condition as the previous study [20] by an Agilent 7890 Gas Chromatography (Agilent Technologies, Santa Clara, USA) equipped with a HP-5 capillary column (30 m  0.32 mm  0.25 mm) and a flame ionization detector.…”
Section: Analysis Of Propionic and Butyric Acidmentioning
confidence: 99%
See 1 more Smart Citation